Chromium Toxicity On Histopathological Changes In The Gill And Liver Of Fresh Water Edible Fingerlings Of Fish, Cyprinus Carpio. - G.TULASI,; K. JAYANTHA RAO, (International Journal of Pharma and Bio Sciences, 2012)
Fingerlings of fishes are very sensitive to a wide variety of toxicants in water and effects of metals. The toxicity of pollutants can be assessed by the extent of histopathological damage to the concentration of the pollutant. In the present study an attempt is made to the impact of aquatic and industrial effluent. Histological analysis of gill and liver revealed the significant morphological alterations such as gill and liver of fish, Cyprinus carpio. Since fishes are the chief sources of nutrition to many parts of the world and their inhabitations are not exceptional from the pollution point of view, the fresh water fish, Cyprinus carpio has been selected as a test species for the present investigation. Moreover fishes are vulnerable especially to the accumulation of abnormal levels of metals in their bodies. Hence, the present study is aimed to understand the mode of toxic action of metals on the non target field fishes like Cyprinus carpio, the metal chosen was Chromium. Fishes were brought from fisheries department, Tirupati, Chittoor district, Andhra Pradesh.